Modeling of a new triangular shape solar distillation system integrated with solar pv panel and dc water heater - Ahsan, Amimul; Ahmad, Nur Syuhada; Riahi, Ali; Uddin, M. Alhaz; Hridoy, Daud Nabi; Shafiquzzaman, M.; Imteaz, Monzur; Idrus, Syazwani; Al-Ansari, Nadhir; Atiq, M.A.U.R.; Ng, Anne (Elsevier, 2023)
A new triangular shape solar distillation system is fabricated using locally available materials by integrating with solar PV panel connected to DC water heater. It is designed for the first time to distill saline water or seawater using solar heat energy directly (to heat sample water) and indirectly (through water heater to heat sample water). The trough is made of Plexiglass and painted in black color which is placed inside the triangular frame made of UPVC pipe. The performance of the still is experimented in field. The diurnal variations of solar heat energy, distillate output, various temperatures and relative humidity are observed. A few linear proportional relationships are obtained between the sunlight heat energy and the productivity, between the ambient temperature and the productivity, and between the productivity and watercover temperature difference. The production rate of the still is higher than the conventional one. An improved simulation model is proposed to estimate the productivity of the still as some previous simulation models cannot estimate the productivity of the solar still precisely. A few new factors are incorporated in the new model as these factors affect the distillate output of the solar still.